Analisa Stablitas Turap Dinding Penahan Tanah di SDN 09 Ranah Pantai Cermin Akibat Beban Statis - Fitria, Winda; Aktorina, Wahyu; Misriani, Merley (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2023)
The rehabilitation and renovation work for school facilities and infrastructures is one of the work programs of the PUPR ministry. SDN 09 Ranah Pantai Cermin is one of the schools in West Sumatera that has the opportunity to take part in this program. This elementary school is located in the Sangir Batang Hari sub- district South Solok Regency. The plan for building classrooms on the edge of a cliff is the main reason for buiding a retaining wall before classroom construction work begins. Turap were built as retaining walls to prevent landslides around the classrooms during pre-construction, constructions and post-construction. Gravity type with river stones as the base material was chosen as a retaining wall at SDN 09 Ranah Pantai Cermin. Gravity turap was chosen as a retaining wall at this school with consideration that there is quite a lot of material around the site and also that work that does not require special skills. Source of data used for soil stability analysis are obtained from the field, previous research and from shop drawings. After analysing data, it was found that the Turap to be built is safe and meets the planning requirements for retaining wall stability with safety factor as follows: overturning 2.3 times, share 11.84 time and with bearing capacity of 16 time calculated by the Terzhagi method. Analysis and checking of the stability of the Turap as retaining wall at SDN 09 Ranah Pantai Cermin is only carried out for static loads on the retaining wall.